Pokémon Go-ing or staying: exploring the effect of age and gender on augmented reality game player experiences in public spaces. Issue 6 (2nd November 2019) - Potts, Ruth; Yee, Lachlan
ABSTRACT: While the benefits of play and discovery in cities have been widely discussed, the impact of augmented reality games, such as Pokémon Go, induced urban discovery on different demographics and their impact on perceptions of public spaces is yet to be studied. This paper examines the perceptions and usage of public spaces by different demographics of augmented reality gamers. The study finds that there are several statistically significant differences between the experiences of men and women, and players of different ages playing Pokémon Go in public spaces in Australia, particularly in their mobility, sense of marginalization and sense of place.